COMPARISON OF THE EFFECTIVENESS OF SCIENTIFIC APPROACH AND PROBLEM-SOLVING APPROACH IN PROBLEM-BASED LEARNING IN CLASS IX OF SMP NEGERI 3 PANGSID - Chairuddin Chairuddin; Farman Farman (USN Kolaka, 2019)
The research used is a quasi-experimental study that aims to determine whether there are differences in the effectiveness of the scientific approach and the problem-solving approach in problem-based learning in class IX students of SMP Negeri 3 Pangsid. The population in this study were all grade IX students of SMP Negeri 3 Pangsid, and the sample consisted of two classes, namely class IX.1 and class IX.2, as an experimental class. Based on data collection from learning outcomes, activities and responses of students show that the mathematics learning outcomes of students in the experimental class 1 are in the high category with a mean of 84.38, student activities in learning can be categorized well, while student responses tend to be positive towards this learning. So, it can be concluded that problem-based learning with the scientific approach is quite active. Student mathematics learning outcomes in experimental class 2 are in the high category with a mean of 79.58, student activity in learning is in right criteria, and tudent responses to this learning are positive. This shows that problem-based learning with a problem-solving approach is quite effective. Hypothesis testing at a significant level ? = 0.05 with the t-test showed a signi ficant difference in effectiveness, in terms oflearning outcomes between students who applied problem-based learning with a scientific approach and students who applied problem-based learning with problem solving approaches.